2006
DOI: 10.31899/hiv2.1027
|View full text |Cite
|
Sign up to set email alerts
|

Reducing AIDS-related stigma and discrimination in Indian hospitals

Abstract: The Population Council is an international, non-profit, nongovernmental institution that seeks to improve the well-being and reproductive health of current and future generations around the world and to help achieve a humane, equitable, and sustainable balance between people and resources. The Council conducts biomedical, social science, and public health research and helps build research capacities in developing countries. Established in 1952, the Council is governed by an international board of trustees. Its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
63
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 8 publications
3
63
2
2
Order By: Relevance
“…Studies show that HIV-related stigma in this context is pernicious, and that its physical and mental health consequences to patients can be damaging [3-7]. Reducing HIV-related stigma in health settings should be a leading priority for health care managers.…”
Section: Reviewmentioning
confidence: 99%
“…Studies show that HIV-related stigma in this context is pernicious, and that its physical and mental health consequences to patients can be damaging [3-7]. Reducing HIV-related stigma in health settings should be a leading priority for health care managers.…”
Section: Reviewmentioning
confidence: 99%
“…These efforts have pointed towards the need for developing interventions that place emphasis on the individuals, facility environments and policies [16, 21]. …”
Section: Introductionmentioning
confidence: 99%
“…9 Studies on stigmatized and discriminatory attitudes toward PLHIV among health care providers (HCPs) have been conducted in some countries. 3,[10][11][12][13][14][15] Some studies found that the levels of stigmatized and discriminatory attitudes were high among HCPs, including HIV testing without informed consent, verbal abuse/gossip, designating patients as HIV positive on charts or in wards, verbally harassing, isolating HIV-positive patients, denial of treatment and using gloves during all interactions. 2,11,14,15 Studies from different countries found that various factors affect stigmatized and discriminatory attitudes toward PLHIV among HCPs.…”
mentioning
confidence: 99%
“…3,[10][11][12][13][14][15] Some studies found that the levels of stigmatized and discriminatory attitudes were high among HCPs, including HIV testing without informed consent, verbal abuse/gossip, designating patients as HIV positive on charts or in wards, verbally harassing, isolating HIV-positive patients, denial of treatment and using gloves during all interactions. 2,11,14,15 Studies from different countries found that various factors affect stigmatized and discriminatory attitudes toward PLHIV among HCPs. Studies in Bangladesh demonstrated that the factors associated with high level of stigmatized and discriminatory attitudes among the HCPs were irrational fears of HIV transmission, working in teaching hospital rather than in nonteaching hospital and diagnostic centers, low level of education, and being male.…”
mentioning
confidence: 99%
See 1 more Smart Citation